Prognostic power of a new index of right ventricle-pulmonary artery coupling based on right ventricular volumes in patients with secondary tricuspid regurgitation. (3rd October 2022) - Cascella, A; Gavazzoni, M; Muraru, D; Heilbron, F; Caravita, S; Tomaselli, M; Parati, G; Badano, L P
Abstract: Background: Although echocardiographic surrogates of right ventricular -arterial coupling (RVAC) have been reported to be associated with outcome in patients with moderate or severe secondary tricuspid regurgitation (STR), pulmonary artery systolic pressure (SPAP) is difficult to be estimated using echocardiography in patients with severe STR. Purpose: Accordingly, we evaluated the predictive power of indexes of RVAC obtained using RV volumes measured using three-dimensional echocardiography (3DE). Methods: We prospectively enrolled 180 patients with moderate or severe STR and complete two-dimensional, Doppler and 3DE data. The composite endpoint of death for any cause and heart failure hospitalization was used as primary outcome. Results: After a median follow up of 24 months (IQR: 2–48), 72 patients (40%) reached the primary endpoint. Most of the echocardiographic parameters of RV function were associated with outcomes. Among the different parameters of RVAC, the receiver operating curve (ROC) analysis selected the ratio between (RV stroke volume [SV]-RegVol)/ RV End-systolic volume (ESV) (i.e. the RV forward SV/ESV) as the best predictor of the combined endpoint (AUC 0.80 [IC 95% 0.73–087]), with a threshold value of 0.49. Event-free survival of patients with RV forward SV/ESV higher and lower 0.49 has been performed (Figure 1). Multivariable Cox proportional hazards models were constructed (Figure 2). Adding sequentially the 3D-RVEF, TAPSE/SPAP and the forward RV SV/RV ESV on top of a basal model made of TR severity, New York Heart Association (NYHA) functional class and tricuspid anulus plane systolic excursion (TAPSE), the χ 2 of the model increased from 40 to 43 (p=0.13) by adding 3D RVEF, from 43 to 46 (p=0.04) by adding TAPSE/SPAP, and from 46 to 51 (p=0.02) by adding RV forward SV/ESV. Severe TR (HR 3.53 [CI 95%: 1.84–6.78], p<0.001) and RV forward SV/ESV <0.49 (HR 2.45 [CI 95% 1.16–5.18], p=0.02) were the only parameters independently associated with outcome. Conclusions: The RV forward SV/ESV is an index of RVAC obtained by 3DE which is independent from SPAP and it is strongly associated with the occurrence of death or heart failure hospitalization in patients with STR. Funding Acknowledgement: Type of funding sources: None.